A study on the investigation of some properties of cheeses supplied from Kastamonu local markets - YILMAZ, Mehmet; ÇELİK, Erdinç; TAHMAS KAHYAOĞLU, Deren (International Society of Academicians, 2023)
In this research, some physicochemical and microbiological analyses were performed on 10 Beyaz cheeses and 10 Lor cheeses obtained from the local markets in Kastamonu in February 2022, and it was determined whether the cheeses met the standards. Moisture, fat, fat in dry matter, protein, salt, salt in dry matter, pH, and titratable acidity values in Beyaz Cheese and Lor cheese samples were determined as 61.36-69.04%, 15.29-8.86%, 39.25-28.43%, 16.61-16.72%, 1.362-0.892%, 3.63-2.87%, 5.75-4.12, 0.150-0.172%, respectively. The average numbers of total aerobic mesophilic bacteria (TAMB), lactic acid bacteria growing on MRS agar, lactobacilli, lactic acid bacteria growing on M17 agar, lactococci, yeast-mold and coliform group bacteria in Beyaz Cheese and Lor cheese samples were determined as 7.89-7.25, 7.31-6.75, 6.93-6.84, 4.20-5.07, 5.70-0.78 log cfu/g, respectively. Based on the findings of the physicochemical analysis, it was found that the cheese samples made in the local markets of Kastamonu generally met the required standards. As a result of the microbiological analysis, coliform group bacteria were found in one of the Lor cheeses. However, coliform group bacteria were detected in all Beyaz cheese samples. These results showed that hygiene could not be ensured in the Beyaz cheese samples.
Keywords: Süt Teknolojisi; Beyaz cheese; Lor cheese; physicochemical; microbiological; Dairy Technology; 2. Zero hunger